Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usahatani Cabai Rawit di Kelurahan Folarora Kota Tidore Kepulauan - Abdul Asiz Ramli; Farid Madjodjo; Muhammad Julham (Peneliti.net, 2022)
This study aims to analyze the feasibility of cayenne pepper farming and the factors that influence the income of cayenne pepper farming in Folarora Village, Tidore Islands City. Data analysis method used is the analysis of production costs, receipts and income and multiple linear regression analysis. The source of data in this study is primary data, obtained from distributing questionnaires to 61 respondents. The results of the study prove that cayenne pepper farming is feasible, because cayenne pepper farming is profitable. In addition, the variables of seed costs, fertilizer costs, pesticide costs, and labor costs, both partially and simultaneously have a significant effect on the income of cayenne pepper farming in Folarora Village, Tidore Islands City.